(untitled) (El-Wahat Journal for Research and Studies, 2021)
The Subject Of The Research Dealt With A Number Of Jurisprudential Rules Governing The Issues And Provisions Of The Claim For Compensation In The Algerian Civil Code, In An Attempt To Investigate The Feasibility Of Using Jurisprudential Rules In The Field Of Legalization Of Legal Issues And Provisions. The Study Concluded After Those Detectives In The Uncovering And Highlighting Of The Facets Of The Various Scientific Applications Of The Jurisprudential Rules. The Obvious Effect Of These Rules Is To Facilitate The Process Of Legalization Of Contemporary Legal Provisions. Hence, This Research Is An Invitation To Enlighten And Guide The Jurisprudential Rules In The Legalization Of The Various Legal And Legal Issues, As They Represent The General Orientations Of Islamic Law For All Time And Place. Key words - Claims of compensation, jurisprudznce rules, responsibility,guarantees